Proximate Composition of Coated Tomato During Storage - Oladiti, Esther Oluyinka; Oluwalana, Isaac Babatunde; Pele, George Ifeoluwa (European Journal of Applied Sciences, 2021)
Postharvest loss is one of the major problems militating against all year access to tomato. This study investigated the proximate composition of tomato coated with gelatin, carboxyl methyl cellulose, honey and alkalinized starch, with uncoated tomatoes serving as control. Moisture content, crude protein, ash, crude fat, crude fibre and carbohydrates were determined during storage of tomato at room temperature. Results showed that the control tomato sample kept for 60 days and the moisture content, crude protein, crude fat, ash, and carbohydrates were 94.56, 0.21, 0.04, 0.15 and 4.98%, respectively. The results also showed that tomato coated with gelatine kept till 69 days and the moisture content, crude protein, crude fat, ash and carbohydrates were 91.89, 0.25, 0.07, 0.13 and 7.53%, respectively. The results further showed that tomato coated with carboxyl methyl cellulose kept for 75 days and the moisture content, crude protein, crude fat, ash and carbohydrates were 91.83, 0.12, 0.05, 0.09 and 7.74%, respectively. Results showed that tomato coated with honey kept for 90 days and the moisture content, crude protein, crude fat, ash and carbohydrates were 89.50, 0.10, 0.05, 0.06 and 10.08%, respectively. Results however showed that tomato coated with alkalinized starch kept for 90 days and the moisture content, crude protein, crude fat, ash and carbohydrates were 89.35, 0.17, 0.05, 0.07 and 10.11%, respectively. The study showed that both honey and alkalinized starch were able to preserve retain appreciable amount of nutrients in tomato for additional 30 days.